Active Learning: Creating Excitement and Enhancing Learning in a Changing Environment of the 21st Century - Fayombo, Grace A. (Mediterranean Journal of Social Sciences, 2012)
The environment is changing very fast, it is reshaping at a rapid pace specifically because the emergence ofnew technologies is changing the society, changing the way we live, the way we communicate and dobusiness and also the way we learn. Consequently, our educational systems are facing significant pressureto change the way we educate our children too in order to adequately prepare them to live, learn, andwork in a global, digital age. Education is all about change and creativity, therefore there should becreative models for engagement in learning in a shifting educational landscape. Education in the 21stcentury is different from what it used to be in the 17th or 18th century because of the changes overtimeand subsequently the variations in the learnersâ€™ needs particularly in this world of technologicaladvancement. Teaching and learning process should be more effective by constant renewal in theknowledge impacted and shared with the students all the time. The mode of instruction delivery needs tochange from traditional teacher-centred to new learning that is learner-centred and globally acceptable asis the case with the USA and other countries where education is undergoing a major paradigm shift(change) from traditional learning environments focused on the teacher as the â€œdelivererâ€ of knowledge tonew open learning environments focused on the learner as information seeker. Although the movement inthe USA and other developed countries took root first at the primary and secondary levels of education, ithas had an impact on tertiary education as well. Likewise, there should be turn of the tide in the NigerianEducational System.